Membangun Strategi Pemasaran Melalui Digital Marketing Instragram dan Tiktok pada UMKM Seblak Opatlima - Leni Sugiyanti; Rendy Permana; Melyona Zenia Rabbil; Yulita Yulita; Donna Hemelia Syahputri (Lembaga Pengembangan Kinerja Dosen, 2025)
As technology rapidly advances and social media adoption becomes widespread, Instagram and TikTok have evolved into essential marketing platforms, particularly for Micro, Small, and Medium Enterprises (MSMEs). This report aims to develop and implement a digital marketing strategy for the Seblak Opat Lima MSME using these two platforms. The business faced challenges in optimizing its digital marketing to reach a broader market, primarily due to a limited understanding of digital marketing among employees and a lack of consistency in social media account management. Our methodology involved field observation, which included creating a content timeline and content scripts to ensure consistency and relevance of published material. The analysis results show a significant increase on both social media platforms after the strategy was implemented, with a growth in followers and enhanced audience engagement, especially on TikTok and Instagram. Furthermore, analytics indicate that trend-aligned content combined with appropriate hashtag usage successfully expanded reach, increased profile visits, and encouraged more active audience interaction. Thus, the implemented digital marketing strategy proved effective in expanding the market and boosting sales for Seblak Opat Lima MSME.